Medico-legal litigation of UK physiotherapists in relation to cauda equina syndrome: a multimethods study. Issue 7 (12th July 2022) - Yeowell, Gillian; Leech, Rachel; Greenhalgh, Susan; Willis, Emma; Selfe, James
Abstract : Objective: The aim was to investigate the extent of cauda equina syndrome (CES) litigation and explore the process of medico-legal litigation in relation to physiotherapy in the UK. Design: A multimethods inquiry that followed on from a previously conducted scoping literature review was undertaken to address the aim. This included freedom of information requests and direct communication with relevant stakeholders and organisations. Results: A total of 2496 CES claims were found in the UK between 2012 and 2020. 51 of these were attributed to physiotherapists. There was little information available to physiotherapists regarding the legal process of litigation and much of this information was not from a physiotherapist's perspective. Conclusion: This is the first study that has investigated the extent and process of CES litigation in physiotherapy in the UK. The extent of CES litigation appears to be high considering CES is a rare spinal condition. Furthermore, the extent of CES litigation is suspected to be considerably higher than the data reported in this study due to the issues identified in how CES claims are recorded. Finally, there is no clearly articulated, easily accessible information describing the process and support available for physiotherapists in receipt of a legal claim.